Covering layer material and high-color-gamut organic electroluminescent device

By using cover material containing nitrogen-oxygen-fused ring structure and narrow spectrum red light dopants in OLED devices, the problem of low red light and green light efficiency in existing OLED products is solved, and the development of high-color gamut OLED devices is achieved, meeting the requirements of the BT2020 standard.

CN119708016APending Publication Date: 2025-03-28BOE TECHNOLOGY GROUP CO LTD
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202510007167.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-02
Publication Date
2025-03-28

AI Technical Summary

Technical Problem

Existing OLED products have low red and green light efficiency in color gamut, which is difficult to meet the requirements of the BT2020 standard.

Method used

The cover material with a fused ring structure containing at least two nitrogen oxide heteroatoms is used to increase the polarization rate, thereby enhancing the refractive index under red light, improving the efficiency of red light, and optimizing the structure of the luminescent layer through narrow spectrum red light dopants and high refractive index cover material.

Benefits of technology

It significantly improves the red light efficiency, realizes the development of high-color gamut OLED devices, and can reach 90% of the BT2020 standard, meeting the display needs of terminal products.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_26
    Figure SMS_26
  • Figure SMS_57
    Figure SMS_57
Patent Text Reader

Abstract

The invention provides a covering layer material and a high-color-gamut organic light-emitting device. The covering layer material comprises a compound shown in the formula (I). The compound contains a fused ring structure of two nitrogen and oxygen heteroatoms, the polarizability can be increased, so that the refractive index under red light is improved, n is larger than or equal to 2.0 at-460 nm, the red light efficiency can be further improved, a high-color-gamut OLED device is obtained, and the current terminal product requirement is met.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of organic light-emitting devices, and in particular to a covering layer material and a high color gamut organic electroluminescent device. Background Art

[0002] Display screens are constantly developing towards high pixels, high color gamut, and low power consumption. At present, due to the increasingly higher requirements for display colors of terminal products such as IT and computer monitors, OLED (organic light-emitting diode) devices are required to continue to develop in the direction of high color gamut. At present, the color gamut of OLED products is far behind the requirements of BT2020 in both red and green light. Therefore, in order to gradually meet the requirements of BT2020, it is necessary to focus on improving the colors of red and green light. According to the sensitivity of the human eye to light, as the color of red light deepens, the efficiency will decrease rapidly. Therefore, the red light efficiency in high color gamut devices will be very low, and improving the red light efficiency has become a key problem. Summary of the invention

[0003] The purpose of the present application is to provide a covering layer material and a high color gamut organic electroluminescent device, wherein the covering layer material used contains at least two fused ring structures of nitrogen and oxygen heteroatoms, which can increase the polarizability, thereby increasing the refractive index under red light, n≥2.0@460nm, and can further improve the red light efficiency to obtain a high color gamut OLED device, thereby meeting the current terminal product needs.

[0004] The first aspect of the present application provides a compound of formula (I):

[0005] in,

[0006] Ar 3 Selected from C 6 -C 20 Aryl, or ;

[0007] L 1 , L 2 , L 3 Each independently selected from a single bond, unsubstituted or substituted C 2 -C 20 Alkylene, unsubstituted or substituted C 6 -C 20 arylene, unsubstituted or substituted C 5 -C 30 heteroarylene;

[0008] X 1 , X 2 , X 3 , X 4Each independently selected from O or S;

[0009] Z 1 , Z 2 , Z 3 Each independently selected from CR 1 or N;

[0010] Y 1 -Y 12 Each independently selected from CR 2 or N; and Z 1 and Y 1 -Y 4 Not N, Z at the same time 2 and Y 5 -Y 8 Not N, Z at the same time 3 and Y 9 -Y 12 Not all are N;

[0011] R 1 , R 2 Each occurrence is independently selected from hydrogen, C 1 -C 10 Alkyl, C 6 -C 20 Aryl, unsubstituted or substituted C 5 -C 20 heteroaryl;

[0012] Ra is independently selected at each occurrence from deuterium, C 2 -C 20 Alkyl, C 6 -C 20 Aryl or C 5 -C 20 heteroaryl;

[0013] The heteroaryl group independently includes one or more heteroatoms selected from N, O or S at each occurrence.

[0014] In some embodiments of the present application, in the compound of formula (I), Ar 3 Selected from naphthyl, phenanthryl, or .

[0015] In some embodiments of the present application, in the compound of formula (I), L 1 , L 2 , L 3 Each independently selected from a single bond, a phenylene group or .

[0016] In some embodiments of the present application, in the compound of formula (I), , and Each independently selected from , , or .

[0017] In some embodiments of the present application, the compound of formula (I) is selected from the compounds shown in the following A1-A31: ; ; ; ; ; ; ; ; ; ; .

[0018] The second aspect of the present application provides a covering layer material, which comprises at least one of the compounds described in the first aspect of the present application.

[0019] The third aspect of the present application provides an organic electroluminescent device, which comprises a covering layer and a light-emitting layer, wherein the covering layer comprises at least one of the compounds described in the first aspect of the present application or the covering layer material described in the second aspect of the present application.

[0020] In some embodiments of the present application, the light-emitting layer includes a red light dopant, and a full width at half maximum in a photoluminescence spectrum of the red light dopant is less than or equal to 38 nm.

[0021] In some embodiments of the present application, the red light dopant is selected from compounds: .

[0022] In some embodiments of the present application, the full width at half maximum of the red light emission peak of the light-emitting layer is less than or equal to 30 nm, and the CIEx is 0.690-0.708.

[0023] The fourth aspect of the present application provides a display device, which comprises at least one of the compounds described in the first aspect of the present application, the covering layer material described in the second aspect of the present application, or the organic electroluminescent device described in the third aspect of the present application.

[0024] Beneficial effects of the present application: The compound provided by the present application includes a fused ring structure containing at least two nitrogen and oxygen heteroatoms, which can increase the polarizability, thereby improving the refractive index under red light, n≥2.0@460nm, and can further improve the red light efficiency; at the same time, a narrow spectrum RD is selected, and the intrinsic PL spectrum FWHM of the RD material is within 38nm, which can improve the front light extraction efficiency; the full width at half maximum (FWHM) of the red light emission peak is controlled to be less than or equal to 30nm, and CIEx is 0.690-0.708, which can reach 90% of BT2020, and obtain a high color gamut OLED device, thereby meeting the current terminal product needs.

[0025] Of course, implementing any product or method of the present application does not necessarily require achieving all of the advantages described above at the same time. DETAILED DESCRIPTION

[0026] The following will be combined with the embodiments of the present application to clearly and completely describe the technical solutions in the present application. Obviously, the described embodiments are only part of the embodiments of the present application, rather than all the embodiments. All other embodiments obtained by those skilled in the art based on the present application belong to the scope of protection of the present application.

[0027] The first aspect of the present application provides a compound of formula (I):

[0028] in,

[0029] Ar 3 Selected from C 6 -C 20 Aryl, or ;

[0030] L 1 , L 2 , L 3 Each independently selected from a single bond, unsubstituted or substituted C 2 -C 20 Alkylene, unsubstituted or substituted C 6 -C 20 arylene, unsubstituted or substituted C 5 -C 30 heteroarylene;

[0031] X 1 , X 2 , X 3 , X 4 Each independently selected from O or S;

[0032] Z 1 , Z 2 , Z 3Each independently selected from CR 1 or N;

[0033] Y 1 -Y 12 Each independently selected from CR 2 or N; and Z 1 and Y 1 -Y 4 Not N, Z at the same time 2 and Y 5 -Y 8 Not N, Z at the same time 3 and Y 9 -Y 12 Not all are N;

[0034] R 1 , R 2 Each occurrence is independently selected from hydrogen, C 1 -C 10 Alkyl, C 6 -C 20 Aryl, unsubstituted or substituted C 5 -C 20 heteroaryl;

[0035] Ra is independently selected at each occurrence from deuterium, C 2 -C 20 Alkyl, C 6 -C 20 Aryl or C 5 -C 20 heteroaryl;

[0036] The heteroaryl group independently includes one or more heteroatoms selected from N, O or S at each occurrence.

[0037] The Z mentioned in this application 1 and Y 1 -Y 4 If it is not N at the same time, it means Z 1 When N, Y 1 -Y 4 Neither N nor Y 1 -Y 4 When at least one is N, Z 1 Not for N. Z 2 and Y 5 -Y 8 If it is not N at the same time, it means Z 2 When N, Y 5 -Y 8 Neither N nor Y 5 -Y 8 When at least one is N, Z 2 Not for N. Z 3 and Y9 -Y 12 If it is not N at the same time, it means Z 3 When N, Y 9 -Y 12 Neither N nor Y 9 -Y 12 When at least one is N, Z 3 Not for N.

[0038] In some embodiments of the present application, in the compound of formula (I), Ar 3 Selected from naphthyl, phenanthryl, or .

[0039] In some embodiments of the present application, in the compound of formula (I), L 1 , L 2 , L 3 Each independently selected from a single bond, a phenylene group or .

[0040] In some embodiments of the present application, in the compound of formula (I), , and Each independently selected from , , or .

[0041] In some embodiments of the present application, the compound of formula (I) is selected from the compounds shown in the following A1-A31: ; ; ; ; ; ; ; ; ; ; .

[0042] The compounds described in the present application include a fused ring structure containing at least two nitrogen and oxygen heteroatoms, which can increase the polarizability, thereby increasing the refractive index under red light, n≥2.0@460nm (refractive index greater than or equal to 2.0 at a wavelength of 460nm), which can further improve the red light efficiency.

[0043] The second aspect of the present application provides a covering layer material, which comprises at least one of the compounds described in the first aspect of the present application.

[0044] The cover layer material is above the cathode and its main function is to improve the light extraction efficiency of the entire OLED device, so the refractive index is a very important parameter. Using at least one of the compounds described in the first aspect of the present application as the cover layer material has a high refractive index and high thermal stability, thereby being able to obtain a high-performance OLED device.

[0045] The third aspect of the present application provides an organic electroluminescent device, which comprises a covering layer and a light-emitting layer, wherein the covering layer comprises at least one of the compounds described in the first aspect of the present application or the covering layer material described in the second aspect of the present application.

[0046] By using at least one of the compounds described in the first aspect of the present application as a covering layer material, the obtained covering layer has a high refractive index and high thermal stability, thereby obtaining a high-performance OLED device.

[0047] In some embodiments of the present application, the light-emitting layer includes a red dopant (RD), and the full width at half maximum (FWHM) in the photoluminescence (PL) spectrum of the red dopant is less than or equal to 38 nm. The present application selects a narrow spectrum RD, and the intrinsic PL spectrum FWHM of the RD material is within 38 nm, which can improve the front light extraction efficiency.

[0048] In some embodiments of the present application, the red light dopant is selected from compound RD-1: .

[0049] In some embodiments of the present application, the full width at half maximum (FWHM) of the red light emission peak of the light-emitting layer is less than or equal to 30nm, and CIEx is 0.690-0.708. The present application controls FWHM and CIEx within the above range to achieve 90% of BT2020 and obtain a high color gamut OLED device, thereby meeting the current terminal product requirements.

[0050] In the present application, there is no particular limitation on the type and structure of the organic electroluminescent device, and it can be any type and structure of organic electroluminescent device known in the art, as long as at least one of the covering layer materials provided in the present application can be used.

[0051] The organic electroluminescent device of the present application may be a light-emitting device with a top-emitting structure, for example, comprising a first electrode (anode), a hole injection layer (HIL), a hole transport layer (HTL), a light-emitting layer (EML), an electron transport layer (ETL), an electron injection layer (EIL), a second electrode (cathode), and a capping layer (CPL) in sequence on a substrate.

[0052] The organic electroluminescent device of the present application may also be a light-emitting device with a double-sided light-emitting structure, for example, a first electrode (anode), a hole injection layer, a hole transport layer, a light-emitting layer, an electron transport layer, an electron injection layer and a second electrode (cathode), and a covering layer are sequentially included on a substrate.

[0053] In addition, an electron blocking layer (EBL) may be provided between the hole transport layer and the light emitting layer, and a hole blocking layer (HBL) may be provided between the light emitting layer and the electron transport layer. However, the structure of the organic electroluminescent device of the present application is not limited to the above specific structure, and the above layers may be omitted or added if necessary.

[0054] The present application has no particular restrictions on the thickness of the above layers, as long as the purpose of the present application can be achieved. For example, an organic electroluminescent device may include a first electrode (anode) (50nm to 100nm) made of metal or metal oxide, a hole injection layer (5nm to 40nm), a hole transport layer (30nm to 130nm), an electron blocking layer (5nm to 80nm), a light-emitting layer (15nm to 80nm), a hole blocking layer (5nm to 20nm), an electron transport layer (5nm to 60nm), an electron injection layer (0.5nm to 3nm), a second electrode (cathode) (10nm to 200nm), and a covering layer (50nm to 80nm) on a substrate in sequence.

[0055] In the organic electroluminescent device of the present application, except for the covering layer comprising the covering material provided by the present application, other layers may use various materials used for the layers in the prior art.

[0056] In the present application, there is no particular limitation on the material of the substrate, and conventional substrates known in the art may be used, such as glass, polymer materials, and glass and polymer materials with thin film transistor (TFT) components.

[0057] In the present application, the material of the first electrode (anode electrode) is not particularly limited, and can be selected from indium tin oxide (ITO), indium zinc oxide (IZO), tin dioxide (SnO 2 ), zinc oxide (ZnO), low temperature polycrystalline silicon (LTPS) and other transparent conductive materials, and can also be selected from metal materials such as silver and its alloys, aluminum and its alloys, and can also be selected from organic conductive materials such as poly (3,4-ethylenedioxythiophene) (PEDOT), or a multilayer structure of the above materials.

[0058] In the present application, the material of the hole injection layer is not particularly limited, and hole injection materials known in the art can be used. For example, hole injection materials known in the art are selected: 1,4,5,8,9,11-hexaazatriphenylhexanitrile (HATCN), 2,3,6,7,10,11-hexacyano-1,4,5,8,9,12-hexaazatriphenylene (HAT-CN), 4-bromo-4-phenyl-diphenylamine (BPBPA), molybdenum trioxide (MoO 3 ) etc. as a hole injection material.

[0059] In the present application, the material of the hole transport layer is not particularly limited and can be selected from hole transport materials known in the art. For example, the hole transport material can be selected from at least one of 4-bromo-4-phenyl-diphenylamine (BPBPA), 4-[1-[4-[di(4-methylphenyl)amino]phenyl]cyclohexyl]-N-(3-methylphenyl)-N-(4-methylphenyl)aniline (TAPC), N,N'-diphenyl-N,N'-(1-naphthyl)-1,1'-biphenyl-4,4'-diamine (NPB), etc.

[0060] In the present application, the material of the electron blocking layer is not particularly limited, and any electron blocking material known in the art may be selected. For example, the electron blocking material may be selected from at least one of 2-methyl-4-chlorobutyric acid (mCPB), tris(4-carbazol-9-ylphenyl)amine (TCTA), and the like.

[0061] In the present application, the blue light-emitting layer may include a host material and a dopant (guest material). The specific materials are not particularly limited and materials known in the art may be selected. For example, the host material (BH) may be (AND), the dopant (BD) may be 1-4-di-[4-(N,N-diphenyl)amino]phenylphenylbenzene (DSA-Ph).

[0062] For the red light-emitting layer, it may include a P-type host material for transporting holes, an N-type host material for transporting electrons, and a dopant (guest material). The specific materials of the P-type host material for transporting holes and the N-type host material for transporting electrons are not particularly limited, and materials known in the art may be selected. For example, the P-type host material for transporting holes (RH-P) may be , the N-type host material (RH-N) that transports electrons can be The dopant (guest material, RD-1) is selected from the narrow spectrum RD material provided in this application.

[0063] For the green light-emitting layer, it may include a P-type host material for transporting holes, an N-type host material for transporting electrons, and a dopant (guest material). The specific materials are not particularly limited, and materials known in the art may be selected. For example, the P-type host material for transporting holes (GH-P) may be , the N-type host material (GH-N) that transports electrons can be ; The dopant (guest material, GD) can be .

[0064] In the present application, there is no particular limitation on the amounts of the host material, the guest material and the dopant, and they may be amounts known to those skilled in the art.

[0065] In the present application, the material of the hole blocking layer is not particularly limited, and hole blocking layer materials known in the art can be used. For example, the hole blocking material can be 1,3,5-tris(1-phenyl-1H-benzimidazol-2-yl) (TPBi).

[0066] In the present application, the material of the electron transport layer is not particularly limited, and electron transport materials known in the art can be used. For example, the electron transport material can be selected from at least one of 1,10-benzodiazolidine (Bphen), 2-[4-(9,10-dinaphtho-2-anthracen-2-yl)phenyl]-1-phenyl-1-benzimidazole (ZADN), 4,6-bis(3,5-di(4-pyridyl)phenyl)-2-methylpyrimidine (B4PyMPM), 3,3'-[5'-[3-(3-pyridyl)phenyl][1,1':3',1'"-terphenyl]-3,3"-diyl]bipyridine (TmPyPb), etc.

[0067] In the present application, the material of the electron injection layer is not particularly limited, and electron injection materials known in the art can be used. For example, the electron injection material can be selected from Liq (8-hydroxyquinoline-lithium), LiF (lithium fluoride), cesium carbonate (CsCO 3 ), metal ytterbium (Yb), etc.

[0068] In the present application, the material of the second electrode (reflective cathode electrode) is not particularly limited, and electron injection materials known in the art can be used. For example, the material of the second electrode (reflective cathode electrode) can be selected from at least one of Al, Mg, Ag, Mg:Ag and the like.

[0069] Specifically, the structure of the organic electroluminescent device includes, in sequence, a first electrode, a hole injection layer (HIL), a hole transport layer (HTL), an electron blocking layer (EBL), a light-emitting layer (EML), a hole blocking layer (HBL), an electron transport layer (ETL), an electron injection layer (EIL), a second electrode, and a capping layer (CPL).

[0070] Red light: The material of the first electrode is ITO; the thickness of HIL is 10nm; the thickness of HTL is 110nm; the thickness of EBL is 75nm; EML is composed of RH and RD, the thickness of the evaporated film layer of RD accounts for 2% of the total thickness of the light-emitting layer, the mass ratio of the P-type main material for transporting holes and the N-type main material for transporting electrons in RH is 5:5, and the thickness of EML is 45nm; the thickness of HBL is 5nm; ETL is composed of ETL material and Liq, the thickness of Liq layer accounts for 50% of the total thickness of ETL, and the thickness of ETL is 30nm; the thickness of EIL is 1nm; the materials of the second electrode are Mg and Ag, and the thickness of the second electrode is 13nm; the thickness of CPL is 65nm.

[0071] Green light: The material of the first electrode is ITO; the thickness of HIL is 10nm; the thickness of HTL is 110nm; the thickness of EBL is 35nm; EML is composed of GH and GD, and the thickness of the evaporated film layer of GD accounts for 8% of the total thickness of the light-emitting layer. The mass ratio of the P-type main material for transporting holes and the N-type main material for transporting electrons in GH is 5:5, and the thickness of EML is 35nm; the thickness of HBL is 5nm; ETL is composed of ETL material and Liq, and the thickness of Liq layer accounts for 50% of the total thickness of ETL, and the thickness of ETL is 30nm; the thickness of EIL is 1nm; the materials of the second electrode are Mg and Ag, and the thickness of the second electrode is 13nm; the thickness of CPL is 65nm.

[0072] Blue light: The material of the first electrode is ITO; the thickness of HIL is 10nm; the thickness of HTL is 110nm; the thickness of EBL is 5nm; EML is composed of BH and BD, the thickness of the evaporated film layer of BD accounts for 3% of the total thickness of the light-emitting layer, and the thickness of EML is 20nm; the thickness of HBL is 5nm; ETL is composed of ETL material and Liq, the thickness of Liq layer accounts for 50% of the total thickness of ETL, and the thickness of ETL is 30nm; the thickness of EIL is 1nm; the materials of the second electrode are Mg and Ag, and the thickness of the second electrode is 13nm; the thickness of CPL is 65nm.

[0073] The present application has no particular limitation on the method for preparing the organic electroluminescent device, and any method known in the art may be used, for example, including but not limited to the following steps:

[0074] (1) cleaning the substrate coated with the first electrode (anode electrode) by one or a combination of chemical washing, water washing, brushing, high-pressure water washing, air knife, UV irradiation, nitrogen treatment, oxygen treatment, etc., and then heating treatment;

[0075] (2) vacuum evaporating a hole injection material on the first electrode (anode electrode) as a hole injection layer;

[0076] (3) vacuum evaporating a hole transport material on the hole injection layer to form a hole transport layer;

[0077] (4) vacuum evaporating an electron blocking material on the hole transport layer as an electron blocking layer;

[0078] (5) vacuum evaporating a light-emitting layer on the electron blocking layer, wherein the light-emitting layer comprises a host material and a guest material;

[0079] (6) vacuum evaporating a hole blocking material on the light-emitting layer as a hole blocking layer;

[0080] (7) vacuum evaporating an electron transport material on the hole blocking layer as an electron transport layer;

[0081] (8) vacuum evaporating an electron injection material on the electron transport layer to form an electron injection layer;

[0082] (9) A cathode material is vacuum evaporated on the electron injection layer to serve as a second electrode (reflective cathode electrode).

[0083] The fourth aspect of the present application provides a display device, which comprises at least one of the compounds described in the first aspect of the present application, the covering layer material described in the second aspect of the present application, or the organic electroluminescent device described in the third aspect of the present application.

[0084] The display device described in this application includes but is not limited to a monitor, a television, a tablet computer, a mobile communication terminal, etc.

[0085] The following examples and comparative examples are given to more specifically describe the embodiments of the present application. Various tests and evaluations were performed according to the following methods. In addition, unless otherwise specified, "parts" and "%" are based on mass.

[0086] Synthesis Example 1: Synthesis of Compound A1

[0087] Under nitrogen atmosphere, benzonaphthofuran-3-amino (1.75 g, 7.5 mmol), 2-(4-bromophenyl)-furanpyridine (4.11 g, 15 mmol), K 2 CO 3 (6.22 g, 45 mmol), 150 mL of toluene solvent, and stirred thoroughly. Add catalyst Pd(PPh 3 ) 4(0.17 g, 0.15 mmol), 25 mL of distilled water, the temperature was raised to reflux, and the reaction was stirred for 10 h. After sufficient reaction, 35 mL of distilled water was added to terminate the reaction, and after cooling, the organic solvent was removed by filtration and reduced pressure distillation to obtain compound A1 with a yield of 76.2%.

[0088] The molecular formula of compound A1 was identified as C 42 H 25 N 3 O 3 ; Mass spectrum m / z: 619.72.

[0089] Synthesis Example 2: Synthesis of Compound A5

[0090] Under nitrogen atmosphere, benzonaphthofuran-3-amino (1.75 g, 7.5 mmol), 2-(4-bromophenyl)-thiophenepyridine (4.35 g, 15 mmol), K 2 CO 3 (6.22 g, 45 mmol), 150 mL of toluene solvent, and stirred thoroughly. Add catalyst Pd(PPh 3 ) 4 (0.17 g, 0.15 mmol), 25 mL of distilled water, the temperature was raised to reflux, and the reaction was stirred for 10 h. After sufficient reaction, 35 mL of distilled water was added to terminate the reaction, and after cooling, the organic solvent was removed by filtration and reduced pressure distillation to obtain compound A5 with a yield of 76.2%.

[0091] The molecular formula of compound A5 was identified as C 42 H 25 N 3 OS 2 ; Mass spectrum m / z: 651.73.

[0092] The synthesis of other compounds can refer to the above synthesis process, and the intermediates can use the raw materials listed in Table 1 below.

[0093] Table 1 Raw materials

[0094] Example 1

[0095] Compounds A1, A5, A16, A22, A24, A26, A31 and control compounds CP-1 and CP-2 were respectively used to deposit thin films on silicon wafers to obtain CPL material films with a thickness of 50 nm. The structural formulas of CP-1 and CP-2 are as follows:

[0096] The absorption coefficient (k) and refractive index (n) of the CPL material film obtained by evaporation were tested using an ellipsometer, and the scanning range of the instrument was 245-1000nm.

[0097] The refractive index of CPL material films prepared from different compounds was compared at three commonly used wavelengths of 460nm, 530nm and 620nm. The results are shown in Table 2.

[0098] Table 2 Comparison of refractive index results

[0099] It can be seen from Table 2 above that the refractive index of the CPL material film obtained by vapor deposition of the compounds A1, A5, A16, A22, A24, A26, and A31 of the present application is significantly higher than the refractive index of the CPL material film obtained by vapor deposition of the reference compounds CP-1 and CP-2.

[0100] In order to protect OLED devices from being damaged by ultraviolet light in the external environment, CPL materials need to have strong absorption ability at around 400nm to absorb external ultraviolet light and prevent device aging. At the same time, they cannot absorb the light emitted by the OLED device itself, so the absorption at 450nm and beyond needs to be almost 0. The absorption coefficients of CPL material films prepared from different compounds are compared at two commonly used wavelengths of 400nm and 450nm. The results are shown in Table 3.

[0101] In addition, the glass transition temperature (Tg) is an important parameter to ensure that the material remains stable during the evaporation process; the glass transition temperature is tested using DSC (differential scanning calorimeter), and the second heating process is selected to test the glass transition temperature value from room temperature to 300°C. The results are shown in Table 3.

[0102] Table 3 Comparison of Absorption Coefficient and Glass Transition Temperature (Tg) Results

[0103] It can be seen from Table 3 above that the CPL material film obtained by evaporating the compounds A1, A5, A16, A22, A24, A26 and A31 of the present application has a strong absorption capacity at around 400nm, and the absorption at 450nm and beyond is almost 0; the glass transition temperature (Tg) is between 122-154°C.

[0104] Example 2

[0105] The ITO substrate is cleaned and dried; HIL material, HTL material, and EBL material are sequentially evaporated on the anode; then the light-emitting layers RH and RD are evaporated; HBL material, ETL material, and EIL material are evaporated on the light-emitting layer; then the cathode is evaporated; and the CPL layer is evaporated on the cathode. The device structure is: HIL (10nm) / HTL (110nm) / EBL (75nm) / RH: RD (45nm, 2%) / HBL (5nm) / ETL: LIQ (30nm, 50%) / EIL (1nm) / Mg: Ag 13nm / CPL 65nm, that is, the material of the first electrode is ITO; the thickness of HIL is 10nm; the thickness of HTL is 110nm; the thickness of EBL is 75nm; EML is composed of RH and RD, the thickness of the evaporated film layer of RD accounts for 2% of the total thickness of the light-emitting layer, and the thickness of EML is 45nm; the thickness of HBL is 5nm; ETL is composed of ETL material and Liq, the thickness of Liq layer accounts for 50% of the total thickness of ETL, and the thickness of ETL is 30nm; the thickness of EIL is 1nm; the materials of the second electrode are Mg and Ag, and the thickness of the second electrode is 13nm; the thickness of CPL is 65nm.

[0106] In all devices, the hole injection layer (HIL) material is HATCN, the hole transport layer (HTL) material is NPB, the hole blocking layer (HBL) material is TPBi, the electron transport layer (ETL) material is Bphen, the electron blocking layer (EBL) material is TCTA, and the electron injection layer (EIL) material is metal ytterbium (Yb). The specific structure is shown below. The P-type host material (RH-P) for transporting holes and the N-type host material (RH-N) for transporting electrons used in the light-emitting layer have the following structures.

[0107] ; .

[0108] The CPL materials used in the devices of different groups are the compounds A1, A24, A31 of the present application and the comparative compounds CP-1 and CP-2 described in Example 1; the RD materials used in the devices of different groups are RD-1 (FWHM in the PL spectrum is 36nm) and comparative RD (FWHM in the PL spectrum is 45nm). The devices of different groups are the same except that the CPL materials and RD materials used are different, as shown in Table 4 below.

[0109]

[0110] Photoelectric performance test of organic electroluminescent devices: Under the same brightness, use a digital source meter and a brightness meter to measure the driving voltage, current efficiency and device life of organic electroluminescent devices prepared with different compounds. Specifically, increase the voltage at a rate of 0.1V per second to measure the brightness of the organic electroluminescent device when it reaches 1000cd / m 2 The voltage at this time is the driving voltage, and the current density at this time is measured at the same time; the ratio of brightness to current density is the current efficiency. The life test is as follows: Use a brightness meter at 1000cd / m 2 Under the brightness, keep a constant current, measure the time for the brightness of the organic electroluminescent device to decay from the initial value to 90%, the unit is h. The test results are shown in Table 4 below.

[0111] Table 4 Comparison of photoelectric performance results of organic electroluminescent devices

[0112] From the above results, it can be seen that the use of the narrow spectrum RD-1 provided by the present application significantly improves the efficiency, indicating that the application of the narrow spectrum RD to deep red devices can improve the device efficiency. In addition, the use of the CPL material with a high refractive index of the present application can further improve the efficiency of red light devices due to its higher refractive index in red light.

[0113] Example 3

[0114] Prepare RGB full-color panel (full-color display), in which the structures of blue light, green light and red light are as follows:

[0115] Blue light: HIL (10nm) / HTL (110nm) / EBL (5nm) / BH: BD (20nm, 3%) / HBL (5nm) / ETL: LIQ (30nm, 50%) / EIL (1nm) / Mg: Ag 13nm / CPL 65nm; that is, the material of the first electrode is ITO; the thickness of HIL is 10nm; the thickness of HTL is 110nm; the thickness of EBL is 5nm; EML is composed of BH and BD, the thickness of the evaporated film layer of BD accounts for 3% of the total thickness of the light-emitting layer, and the thickness of EML is 20nm; the thickness of HBL is 5nm; ETL is composed of ETL material and Liq, the thickness of Liq layer accounts for 50% of the total thickness of ETL, and the thickness of ETL is 30nm; the thickness of EIL is 1nm; the materials of the second electrode are Mg and Ag, and the thickness of the second electrode is 13nm; the thickness of CPL is 65nm.

[0116] Green light: HIL (10nm) / HTL (110nm) / EBL (35nm) / GH: GD (35nm, 5:5, 8%) / HBL (5nm) / ETL: LIQ (30nm, 50%) / EIL (1nm) / Mg: Ag 13nm / CPL 65nm; that is, the material of the first electrode is ITO; the thickness of HIL is 10nm; the thickness of HTL is 110nm; the thickness of EBL is 35nm; EML is composed of GH and GD, the thickness of the evaporated film layer of GD accounts for 8% of the total thickness of the light-emitting layer, the mass ratio of the P-type main material for transporting holes and the N-type main material for transporting electrons in GH is 5:5, the thickness of EML is 35nm; the thickness of HBL is 5nm; ETL is composed of ETL material and Liq, the thickness of Liq layer accounts for 50% of the total thickness of ETL, the thickness of ETL is 30nm; the thickness of EIL is 1nm; the materials of the second electrode are Mg and Ag, the thickness of the second electrode is 13nm; the thickness of CPL is 65nm.

[0117] Red light: HIL (10nm) / HTL (110nm) / EBL (75nm) / RH: RD (45nm, 5:5, 2%) / HBL (5nm) / ETL: LIQ (30nm, 50%) / EIL (1nm) / Mg: Ag 13nm / CPL 65nm; that is, the material of the first electrode is ITO; the thickness of HIL is 10nm; the thickness of HTL is 110nm; the thickness of EBL is 75nm; EML is composed of RH and RD, the thickness of the evaporated film layer of RD accounts for 2% of the total thickness of the light-emitting layer, the mass ratio of the P-type main material for transporting holes and the N-type main material for transporting electrons in RH is 5:5, the thickness of EML is 45nm; the thickness of HBL is 5nm; ETL is composed of ETL material and Liq, the thickness of Liq layer accounts for 50% of the total thickness of ETL, the thickness of ETL is 30nm; the thickness of EIL is 1nm; the materials of the second electrode are Mg and Ag, the thickness of the second electrode is 13nm; the thickness of CPL is 65nm.

[0118] In all panels, the hole injection layer (HIL) material is HATCN, the hole transport layer (HTL) material is NPB, the hole blocking layer (HBL) material is TPBi, the electron transport layer (ETL) material is Bphen, the electron blocking layer (EBL) material is TCTA, and the electron injection layer (EIL) material is metal ytterbium (Yb), and the specific structure is shown in Example 2. The P-type host material (RH-P) for transporting holes and the N-type host material (RH-N) for transporting electrons used in the red light emitting layer have the structural formula shown in Example 2; the host material (BH) used in the blue light emitting layer is AND, and the guest material (BD) is DSA-Ph, and the structural formula is shown below; the P-type host material (GH-P) for transporting holes, the N-type host material (GH-N) for transporting electrons, and the guest material (GD) used in the green light emitting layer have the structural formula shown below.

[0119] ; .

[0120] The blue light emitting layer and green light emitting layer of the panels of different groups are the same, and only the red light emitting layer is changed. The red light emitting layer is the same except that the CPL material and RD material used are different, as shown in Table 5 below.

[0121] The CPL materials selected for different groups of panels are compounds A1, A24, A31 of the present application and comparative compounds CP-1 and CP-2 described in Example 1; the RD materials selected for different groups of panels are RD-1 (FWHM in PL spectrum is 36 nm) and comparative RD (structure as described in Example 2, FWHM in PL spectrum is 45 nm).

[0122] BT2020 ratio detection of RGB full-color panel: Use PR680 high-sensitivity dual-channel photometer to test and obtain the color coordinates of the three RGB colors. The ratio of BT2020 is calculated by color coordinates. The test results are shown in Table 5 below.

[0123] Table 5 Comparison of BT2020 ratio detection results of RGB full-color panel

[0124] It can be seen from the above results that by using the narrow spectrum RD-1 provided in this application and the CPL material with a high refractive index, the RGB full-color panel prepared can reach 91% BT2020.

[0125] The above description is only a preferred embodiment of the present application and is not intended to limit the present application. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present application shall be included in the scope of protection of the present application.

Claims

1. A compound of formula (I): in, Ar3 is selected from C6-C 20 Aryl, or ; L1, L2, L3 are each independently selected from a single bond, unsubstituted or Ra-substituted C2-C 20 Alkylene, unsubstituted or substituted C6-C 20 arylene, unsubstituted or substituted C5-C 30 heteroarylene; X1, X2, X3, X4 are each independently selected from O or S; Z1, Z2, Z3 are each independently selected from CR1 or N; Y1-Y 12 are independently selected from CR2 or N; and Z1 and Y1-Y4 are not N at the same time, Z2 and Y5-Y8 are not N at the same time, and Z3 and Y9-Y 12 Not all are N; R1, R2, at each occurrence, are independently selected from hydrogen, C1-C 10 Alkyl, C6-C 20 Aryl, unsubstituted or substituted C5-C 20 heteroaryl; Ra is independently selected at each occurrence from deuterium, C2-C 20 Alkyl, C6-C 20 Aryl or C5-C 20 heteroaryl; The heteroaryl group independently includes one or more heteroatoms selected from N, O or S at each occurrence.

2. The compound according to claim 1, wherein Ar3 is selected from naphthyl, phenanthrenyl, or .

3. The compound according to claim 1, wherein L1, L2, L3 are each independently selected from a single bond, a phenylene group or .

4. The compound according to claim 1, wherein , and Each independently selected from , , or .

5. The compound according to claim 1, wherein The compound is selected from the following compounds A1-A31: 。 6. A covering material comprising at least one of the compounds according to any one of claims 1 to 5.

7. An organic electroluminescent device comprising a covering layer and a light-emitting layer, wherein the covering layer comprises at least one of the compounds according to any one of claims 1 to 5 or the covering layer material according to claim 6.

8. The organic electroluminescent device according to claim 7, wherein: The light-emitting layer includes a red light dopant, and the full width at half maximum in the photoluminescence spectrum of the red light dopant is less than or equal to 38 nm; Preferably, the red light dopant is selected from compounds: 。 9. The organic electroluminescent device according to claim 7 or 8, wherein: The full width at half maximum of the red light emission peak of the light-emitting layer is less than or equal to 30 nm, and the CIEx is 0.690-0.

708.

10. A display device comprising at least one of the compounds according to any one of claims 1 to 5, the covering layer material according to claim 6 or the organic electroluminescent device according to any one of claims 7 to 9.

Citation Information

Cited By

  • Organic compound, composition, light-emitting device, and display device

    CN121405715A